Bajidoran: Bentuk Pertunjukan Kemasan Seni Wisata di Angkringan Teh Ita Kota Bandung - Azizah, Farah Nurul; Nuriawati, Risa (Universitas Sultan Ageng Tirtayasa, 2024)
Bajidoran, one of the folk arts in West Java, is now not only present on village celebration stages. The latest phenomenon, Bajidoran is now being packaged into a show at a tourist spot, namely Angkringan Teh Ita. Bajidoran grows and develops in the midst of urban society with the concept of tourism art packaging, which of course has a different form of performance from that in its original habitus. This article wants to explain the form of the Bajidoran performance with the concept of tourist art packaging, using qualitative research methods. The data collection techniques used were field observation, in-depth interviews, literature study and documentation study. An explanation of the Bajidoran performance, using the concepts of tourism art packaging, including: 1) making an imitation of the original, 2) Short or concise, or a mini form of the original, 3) full of variations, 4) abandoning sacred and magical values , as well as its symbols, and 5) it is cheap. Bajidoran's presence at Angkringan Teh Ita is also supported by several factors, including people, performance venues and promotions.